Assessment of a Possible Link Between Hyperhomocysteinemia and Hyperuricemia. Issue 3 (1st March 2015) - Cohen, Eytan; Levi, Amos; Vecht-Lifshitz, Susan E.; Goldberg, Elad; Garty, Moshe; Krause, Ilan
Abstract : Background/Aim: Hyperhomocysteinemia and hyperuricemia are both considered risk factors for coronary artery disease. However, the relationship between the 2 has not yet been thoroughly investigated. This study aimed to evaluate this relationship more closely. Material and Methods: This study is a retrospective cross-sectional analysis of data from a screening center in Israel assessing 16, 477 subjects, within an age range of 20 to 80 years. Results: The mean age of the study sample was 46 years, and 68% were males. Hyperuricemia was found in 24.9% and 14.6% of subjects with elevated and normal homocysteine serum levels, respectively ( P < 0.001). A positive association was found between homocysteine serum levels and uric acid serum levels. Compared with subjects with normal homocysteine serum levels, those with hyperhomocysteinemia had an odds ratio (OR) for hyperuricemia of 1.7 (95% confidence interval [CI], 1.5–1.9) and 1.6 (95% CI, 1.1–2.5) for males and females, respectively. After multivariate adjustment for age, hypertension, body mass index, estimated glomerular filtration rate, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, and thiazide use, the association remained significant in males (OR, 1.5; 95% CI, 1.3–1.7; P < 0.001) but not in females (OR, 0.9; 95% CI, 0.6–1.6; P = 0.82). Conclusions: This large cohort showed a significant association between hyperhomocysteinemia and hyperuricemia. Sex differences were observed. This study suggests that accelerated atherosclerosis may be a consequence of the combined effect of these 2 factors.